Approaches and styles of mothers in sex education process of children and the related factors - Elnaz Faraji Nesfechi; Moluk Pouralizadeh; Zahra Bostani Khalesi; Saman Maroufizadeh (BMC, 2023)
Abstract Introduction Sex education supports the development of suitable sexual behaviors in children. However, due to the limitations of sexual issues in Iran, parents may have different sex education styles. This study aimed to assess the styles of mothers in the sex education process of children and the related factors. Methods In a cross-sectional study, from March to May 2021, 306 mothers with a 4-12-year-old child who were referred to the comprehensive health service centers in Rasht city were entered into the study by a convenience sampling method. The tool was a questionnaire of parents' sex education styles. Data analysis was performed with independent t-tests, one-way ANOVA, Pearson's correlation coefficient, and the multiple linear regression model using SPSS software version 16. Results The majority of the mothers had a mean age of 36.2 ± 6.4 years. The score of the authoritarian sex education style was significantly higher than the other styles (P < 0.001). According to the multivariate analysis, 40.6% of the changes in the strict style (R2 = 0.406), 32.7% of the changes in the permissive style (R2 = 0.327), and 36.1% of the changes in the authoritative style (R2 = 0.361) were explained by the personal characteristics of the participants. Conclusion The authoritative style was a dominant sex education style. Identifying the factors associated with types of child sex education styles has an important role in promoting the health of children and the community. It is recommended that nursing policymakers identify related factors of sex education styles in mothers of different cultures, and therefore, implement training programs for empowering mothers.